Evaluation of Continuous Inhaled Epoprostenol in the Treatment of Acute Respiratory Distress Syndrome, Including Patients With SARS-CoV-2 Infection. Issue 10 (October 2022) - Niss, Hannah L.; Mohamed, Adham; Berry, Timothy P.; Saettele, Timothy M.; Haines, Michelle M.; Thomas, Elizabeth L.
Background: Acute respiratory distress syndrome (ARDS) management is primarily supportive. Pulmonary vasodilators, such as inhaled epoprostenol (iEPO), have been shown to improve PaO2 :FiO2 (PF) and are used as adjunctive therapy. Objective: To identify the positive response rate and variables associated with response to iEPO in adults with ARDS. A positive response to iEPO was defined as a 10% improvement in PF within 6 hours. Methods: This retrospective study included adults with ARDS treated with iEPO. The primary endpoint was the variables associated with a positive response to iEPO. Secondary endpoints were positive response rate and the change in PF and SpO2 :FiO2 within 6 hours. Statistical analysis included multivariable regression. Results: Three hundred thirty-one patients were included. As baseline PF increased, the odds of responding to iEPO decreased (odds ratio [OR], 0.752, 95% CI, 0.69-0.819, p < 0.001). Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2)-related ARDS (OR 0.478, 95% CI, 0.281-0.814, p = 0.007) was associated with decreased odds of a positive response to iEPO. The total population had a 68.3% positive response rate to iEPO. SARS-CoV-2-related ARDS and non-SARS-CoV-2-related ARDS had a 59.5% and 72.7% positive response rate, respectively. iEPO significantly improved PF (71 vs 95, P < 0.001) in the whole population. Conclusion and Relevance: iEPO was associated with a positive effect in a majority of moderate-to-severe ARDS patients, including patients with SARS-CoV-2-related ARDS. Lower baseline PF and non-SARS-CoV-2-related ARDS were significantly associated with a positive response to iEPO. The ability to predict which patients will respond to iEPO can facilitate better utilization.